In Which Exchange Rate Models Do Forecasters Trust? - Lee, Jaewoo; Hauner, David; Takizawa, H. (Washington, D.C. : International Monetary Fund, 2011)
Using survey data of market expectations, we ask which popular exchange rate models appear to be consistent with expectation formation of market forecasters. Exchange rate expectations are found to be correlated with inflation differentials and productivity differentials, indicating that the relative PPP and Balassa-Samuelson effect are common inputs into expectation formation of market forecasters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet